The effect of FTO variation on increased osteoarthritis risk is mediated through body mass index: a mendelian randomisation study. Issue 12 (6th August 2013) - Panoutsopoulou, Kalliope; Metrustry, Sarah; Doherty, Sally A; Laslett, Laura L; Maciewicz, Rose A; Hart, Deborah J; Zhang, Weiya; Muir, Kenneth R; Wheeler, Margaret; Cooper, Cyrus; Spector, Tim D; Cicuttini, Flavia M; et al.
Abstract : Objective: Variation in the fat mass and obesity-associated ( FTO ) gene influences susceptibility to obesity. A variant in the FTO gene has been implicated in genetic risk to osteoarthritis (OA). We examined the role of the FTO polymorphism rs8044769 in risk of knee and hip OA in cases and controls incorporating body mass index (BMI) information. Methods: 5409 knee OA patients, 4355 hip OA patients and up to 5362 healthy controls from 7 independent cohorts from the UK and Australia were genotyped for rs8044769. The association of the FTO variant with OA was investigated in case/control analyses with and without BMI adjustment and in analyses matched for BMI category. A mendelian randomisation approach was employed using the FTO variant as the instrumental variable to evaluate the role of overweight on OA. Results: In the meta-analysis of all overweight (BMI≥25) samples versus normal-weight controls irrespective of OA status the association of rs8044769 with overweight is highly significant (OR[CIs] for allele G=1.14 [01.08 to 1.19], p=7.5×10 −7 ). A significant association with knee OA is present in the analysis without BMI adjustment (OR[CIs]=1.08[1.02 to 1.14], p=0.009) but the signal fully attenuates after BMI adjustment (OR[CIs]=0.99[0.93 to 1.05], p=0.666). We observe no evidence for association in the BMI-matched meta-analyses. Using mendelian randomisation approaches we confirm the causal role of overweight on OA. Conclusions: Our data highlight the contribution of genetic risk to overweight in defining risk to OA but the association is exclusively mediated by the effect on BMI. This is consistent with what is known of the biology of the FTO gene and supports the causative role of high BMI in OA.